2012
DOI: 10.12816/0003118
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Presentation of Oral Squamous Cell Carcinoma in a Young Woman = عرض غير عادي لسرطان الخلايا الحرشفية في الفم عند إمرأة شابة

Abstract: Oral squamous cell carcinoma (OSCC) is the most common oral malignant neoplasm, mainly affecting individuals over 50 years old with a history of tobacco and alcohol use. The occurrence of this oral cancer in individuals under 40 years old is unusual and, when it does occur, shows a weaker relation to those risk factors and a more aggressive clinical course. Due to the paucity of reports in this population, it is difficult to prove its increasing trend. A case of oral squamous cell carcinoma in a 39-year-old wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The 5‐year survival rate has not improved over the last few decades regardless of improvements in surgical and oncological treatments. A large majority of oral cancers (>90%) are oral squamous cell carcinoma (OSCC), with one of the biggest obstacles to improvement in prognosis being the delayed presentation of disease, as evidenced by the fact that survival for stage I OSCC is 80%, which reduces to 20–30% for stage IV disease [ 2 , 3 ]. OSCC is caused by a multitude of genetic and environmental factors and is preceded in a majority of cases by a potentially malignant state with proliferation of atypical epithelium known as oral epithelial dysplasia (OED) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The 5‐year survival rate has not improved over the last few decades regardless of improvements in surgical and oncological treatments. A large majority of oral cancers (>90%) are oral squamous cell carcinoma (OSCC), with one of the biggest obstacles to improvement in prognosis being the delayed presentation of disease, as evidenced by the fact that survival for stage I OSCC is 80%, which reduces to 20–30% for stage IV disease [ 2 , 3 ]. OSCC is caused by a multitude of genetic and environmental factors and is preceded in a majority of cases by a potentially malignant state with proliferation of atypical epithelium known as oral epithelial dysplasia (OED) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oral squamous cell carcinoma (OSCC) is typically regarded to be a disease that predominantly affects older males ( 1 , 2 ). Intriguingly, recent studies have shown an increase in the incidence of OSCC in young female patients without the well-known causes of OSCC like alcohol and tobacco abuse ( 2 - 4 ). The etiology and pathogenesis of oral cavity cancer in young female patients could be different from those occurring in older patients ( 3 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…The secondary prevention strategy is encouraging people who have been exposed to risk factors to submit to an oral mucosa examination. However, there is an increasing trend for young women diagnosed with OSCC to show no correlation with ABC risk factors [ 3 ]. Their oral health condition is ignored and neglected under the criteria of secondary prevention, causing them to delay seeking medical attention.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive alcohol consumption, betel quid chewing, and cigarette smoking (ABC habits) are risk factors for oral cancer [ 2 ]. However, the ABC habits cannot explain the increasing trend of young females diagnosed with oral squamous cell carcinoma (OSCC) without performing the ABC habits [ 3 ].…”
Section: Introductionmentioning
confidence: 99%